Primary intravitreal bevacizumab for the management of pseudophakic cystoid macular edema Pilot study of the Pan-American Collaborative Retina Study Group (2007)
To determine the feasibility, safety, and clinical effect of primary intravitreal bevacizumab (Avastin) in patients with cystoid macular edema (CME) after cataract surgery. Five institutions in Venezuela, Costa Rica, Puerto Rico, Peru, and Brazil. Twenty-eight eyes of 25 patients treated with at least 1 intravitreal injection of 1.25 mg or 2.50 mg of Avastin participated in this interventional retrospective multicenter study at 5 institutions from 5 countries. Baseline and follow-up visits included Early Treatment Diabetic Retinopathy Study (ETDRS) visual acuity testing, optical coherence tomography (OCT) imaging, and ophthalmoscopic examination. The mean follow-up was 32 weeks (range 24 to 52 weeks). Twenty eyes (71.4%) had improved best corrected visual acuity (BCVA) (R2 ETDRS lines), and no eye had worse visual acuity (R2 ETDRS lines). The BCVA remained stable in 8 eyes (28.6%). The mean baseline BCVA was 20/160 (logMAR Z 0.92) and the mean final BCVA, 20/63 (logMAR Z 0.50); the difference was statistically significant (P<.0001). The mean central macular thickness at baseline (466.3 mm; range 208 to 784 mm) decreased significantly (264.5 mm; range 176 to 513 mm) by the end of follow-up (P<.0001). Eight eyes (28.6%) required a second injection and 4 (14.3%), a third injection. The mean interval between injections was 13 weeks (range 5 to 26 weeks). No ocular or systemic adverse events were observed. Short-term results suggest that primary intravitreal Avastin is well tolerated in patients with pseudophakic CME. Treated eyes had a significant improvement in BCVA and decrease in macular thickness by OCT.